Brassinosteroid Deficiency Due to Truncated Steroid 5α-Reductase Causes Dwarfism in the lk Mutant of Pea - Nomura, Takahito (American Society of Plant Biologists, 2004)
The endogenous brassinosteroids in the dwarf mutant lk of pea (Pisum sativum) were quantified by gas chromatography-selected ion monitoring. The levels of castasterone, 6-deoxocastasterone, and 6-deoxotyphasterol in lk shoots were reduced 4-, 70-, and 6-fold, respectively, compared with those of the wild type. The fact that the application of brassinolide restored the growth of the mutant indicated that the dwarf mutant lk is brassinosteroid deficient. Gas chromatography-selected ion monitoring analysis of the endogenous sterols in lk shoots revealed that the levels of campestanol and sitostanol were reduced 160- and 10-fold, respectively, compared with those of wild-type plants. These data, along with metabolic studies, showed that the lk mutant has a defect in the conversion of campest-4-en-3-one to 5α-campestan-3-one, which is a key hydrogenation step in the synthesis of campestanol from campesterol. This defect is the same as that found in the Arabidopsis det2 mutant and the Ipomoea nil kbt mutant. The pea gene homologous to the DET2 gene, PsDET2, was cloned, and it was found that the lk mutation would result in a putative truncated PsDET2 protein. Thus it was concluded that the short stature of the lk mutant is due to a defect in the steroidal 5α-reductase gene. This defect was also observed in the callus induced from the lk mutant. Biosynthetic pathways involved in the conversion of campesterol to campestanol are discussed in detail.